Unveiling English Speaking Competence: A Portrait of First-Semester Students in the Foreign Language Development Program - Wafi, Abdul; Febrianingrum, Lasmi; Rahmawati, Fithriyah (PANYONARA: Journal of English Education, 2025)
This research delves into the English-speaking competence of first-semester students enrolled in the Foreign Language Development Program (FLDP) at IAIN Madura. Through a survey of 279 students across four faculties, the study investigates the current state of English-speaking proficiency and identifies factors influencing it. The findings reveal that a majority of students self-rate their speaking skills as basic, with limitations in vocabulary, pronunciation, and confidence hindering their fluency. This highlights the need for targeted interventions, including increased speaking practice, vocabulary instruction, and a supportive classroom environment to enhance students' English-speaking competence and prepare them for academic and professional communication in a globalized world. The study identifies key factors influencing speaking fluency, including lack of self-confidence, low motivation, and limited prior exposure to English. It emphasizes the importance of addressing these factors through effective language instruction, incorporating task-based learning, communicative approaches, and providing adequate institutional support. The research underscores the need for a comprehensive approach to language instruction that prioritizes increased speaking practice, vocabulary instruction, and a supportive classroom environment to improve students' English-speaking competence and prepare them for the demands of academic and professional communication in a globalized world.